(3Yde GdeYdheGJ (B/s - (3GdUHGZ, YeGO YHO GdhgGHs ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2004)
(3eaGgje YGeI(B- (3JWhQ Yde GdeYdheGJ(B- (3GdeYGdLI GdMGShHjI ddHjGfGJ(B- (3GdeaGgje GdGSGSjI dfXe GdeYdheGJ(B- (3fXGe GdeYdheGJ GdESJQGJjLj(B- (3fbGW egeI aj JcfhdhLjG GdeYdheGJ(B- (3CefjI JcfhdhLjG GdeYdheGJ(B.s
Keywords: (3Yde GdeYdheGJs